Effective thermal expansion coefficient of a sintered glass–eucryptite composite; Journal of Materials Science; Vol. 52, iss. 19 - Kryukova O. N. Olga Nikolaevna; Knyazeva A. G. Anna Georgievna; Pogrebenkov V. M. Valery Matveevich; Kostikov K. S. Kirill Sergeevich; Sevostjyanov I. B. Igor Borisovich (2017, 2017)
Title screen